PENERAPAN MODEL PEMBELAJARAN TIPE TGT (TEAMS GAMES TOURNAMENTS) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN PEKERJAAN DASAR TEKNIK OTOMOTIF PADA SISWA SMK NEGERI 1 INDRALAYA UTARA - Adam Salam Rudiantono; Harlin Harlin; Darlius Darlius (JURNAL PENDIDIKAN TEKNIK MESIN, 2017)
Abstract:This research is a classroom action research (PTK) using model Team Game Tournamen on subjects Basic Works Automotive Engineering Class X TKR 3 SMK Negeri 1 North Indralaya. Aiming fatherly increase the activity and student learning outcomes subjects Basic Works Automotive Engineering Class X TKR 3 SMK Negeri 1 North Indralaya. The subjects were students of class X TKR 3 and the object of this study is a model Team Game Tournamen. This research was carried out in three cycles consisting of three meetings. Based on the results before the given action (T0) amounted to 40.55% with an average of 62.16, while after a given action (T1) in the first cycle of 51.35% with an average of 64.86, whereas (T2) in cycle II amounted to 72.97% with an average of 73.24 and (T3) in the third cycle of 86.48% with an average of 80.54. As for the activity of students in the first cycle of 34.71%, in the second cycle of 52.59% and in the third cycle of 66.52%. Of the three cycles showed increased activity and student learning outcomes. Keywords: Game Tournament Team Model, Motivation and Learning Outcomes